ACCOUNTING RESEARCH. - Davidson, Sidney (The Accounting Review, 1957)
The full value of the internal auditor's work can be realized by management only if the findings and recommendations of the auditor are clearly communicated to management. In the early days of internal auditing, reports frequently followed the pattern set by long-form reports of public accountants. In the last fifteen years there has been a remarkable change in the concept of the proper functions of an internal auditor. When a company has sustained a loss in a previous year, this loss may be used to offset taxable income for the succeeding five years. In September, 1950 the Committee on Accounting Procedure of the American Institute of Accountants issued a bulletin dealing with Business Combinations or, as they are more commonly known, pooling of interests. The bulletin dealt with those situations involving issuance of capital stock for assets or capital stock of another company where the transaction might more appropriately be dealt with as a pooling of interest, rather than in accordance with the general rule that such issuances constituted acquisitions of assets, as they would if the consideration given was cash rather than stock.